A carbon allotrope with twisted Dirac cones induced by grain boundaries composed of pentagons and octagons. Issue 5 (20th January 2023) - Kong, Weixiang; Xiao, Xiaoliang; Zhan, Fangyang; Wang, Rui; Gan, Li-Yong; Wei, Juan; Fan, Jing; Wu, Xiaozhi
Abstract : A class of monolayer carbon allotropes are proposed. These structures exhibit attractive transport properties such as Van Hove singularity and quasi-one-dimensional metallic wires. Abstract : The grain boundaries (GBs) composed of pentagons and octagons (558 GBs) have been demonstrated to induce attractive transport properties such as Van Hove singularity (VHS) and quasi-one-dimensional metallic wires. Here, we propose a monolayer carbon allotrope which is formed from the introduction of periodic 558 GBs to decorate intact graphene, termed as PHO-graphene. The calculated electronic properties indicate that PHO-graphene not only inherits the previously superior characteristics such as Van Hove singularity and quasi-one-dimensional metallic wires, but also possesses two twisted Dirac cones near the Fermi level. Further calculation finds that the Berry phase is quantized to ± π at the two Dirac points, which is consistent with the distribution of the corresponding Berry curvature. The parity argument uncovers that PHO-graphene hosts a nontrivial band topology and the edge states connecting the two Dirac points are clearly visible. Our findings not only provide a reliable avenue to realize the abundant and extraordinary properties of carbon allotropes, but also offer an attractive approach for designing all carbon-based devices.